MANAGING EMPLOYEE RECRUITMENT PROCESSES IN THE MINISTRY OF HEALTH IN BOTSWANA - ZHIRO, KEDIBONYE (My University, 2012)
Employee recruitment plays a key role in attracting workforce to organizations. However, fulfilling recruitment objectives is never an easy task for many organizations especially those in the public sector. The Ministry of Health in Botswana is not an exception as evidenced by its inability to reach its targeted vacancy rate of 2% on a quarterly basis over time. This study undertook to explore challenges encountered by the Ministry of Health in Botswana in its effort to recruit adequate qualified number of employees with a focus on the recruitment methods used. In addition, the recommendations were made on how the Ministry can improve its recruitment processes and hence acquire the desired number of employees. A qualitative research approach and a case study research design were employed. Purposive sampling was used. Seven respondents well-versed on recruitment issues were interviewed and vacancy rates reports were reviewed. The study established that although the Ministry uses a variety of recruitment methods, it is constrained by several challenges. The identified challenges range from procedural requirements, recruitment methods shortcomings and organizational factors. The study recommends a review of the procedural requirements, active use of informal methods alongside advertisement, review of the pay structures and establishment of dedicated recruitment enquiry desk(s). A similar research with a broader focus is proposed for future investigation
MM thesis - P&DM
Keywords: Staff selection; Selection of staff; Personnel selection; Recruitment of staff